Hemp seeds: Nutritional value, associated bioactivities and the potential food applications in the Colombian context - Montero, Lidia; Ballesteros-Vivas, Diego; Gonzalez-Barrios, Andrés Fernando; Sánchez-Camargo, Andrea del Pilar (Frontiers in Nutrition, 2023)
For many years, Colombia was one of the countries with the largest illegal cultivation of cannabis around the world. Currently, it is going through a period of transition with a new government law that recently allows the cultivation, transformation, and commercialization of such plant species. In this sense, the identification of strategies for the valorization of products or by-products from Cannabis sativa represent a great opportunity to improve the value chain of this crop. One of these products is hemp seeds, which are exceptionally nutritious and rich in healthy lipids (with high content of three polyunsaturated fatty acids: linoleic acid, alpha-linolenic acid, and gamma-linolenic acid), good quality protein, and several minerals. In addition, hemp seeds contain THC (tetrahydrocannabinol) or CBD (cannabidiol) in traces, molecules that are responsible for the psychoactive and therapeutic properties of cannabis. These low terpenophenolic contents make it more attractive for food applications. This fact, together with the constant search for proteins of vegetable origin and natural food ingredients, have aroused an important interest in the study of this biomass. Some bioactivities of phytochemical compounds (polyphenols and terpenoids, mainly) present in hemp seeds have provided antioxidant, antimicrobial, and anti-inflammatory properties. This review summarizes and discusses the context of hemp use in Latin-American and the new opportunities for hemp seeds culture in Colombia considering the valuable nutritional value, main functional bioactivities, and recent advances in food market applications of hemp seeds.